Revolutionizing Student Discipline: Strategic Management Approaches for Secondary Schools - Rossa, Ade Tutty Rokhayati; Oktavia, Fany; Cahyani, Ratih; Sodiran, Sodiran (Journal of Educational Management Research, 2025)
Student discipline plays a crucial role in the success of secondary schools, where academic and social pressures frequently give rise to behavioral challenges. Issues such as truancy, tardiness, and rule violations hinder learning and disrupt the educational environment. This study examines how strategic management can improve student discipline in secondary schools, employing a qualitative research approach. Data were gathered through literature reviews and case studies across several institutions. Key strategies include data-driven discipline planning, active student organization involvement (OSIS, MPK, Scouts), optimizing homeroom teacher roles by Ministry of Education Regulation No. 25 of 2024, implementing a point-based reward and punishment system, and utilizing digital attendance and monitoring tools. Findings show that when strategically implemented, these approaches foster a favorable, sustainable discipline climate, reduce infractions, and improve educational quality. The study emphasizes the significance of strong leadership, character education, and community collaboration in cultivating responsible and disciplined students who are well-equipped for future challenges.